DESIGN EXPERIENTIAL MARKETING MODELS ON SMALL AND MEDIUM BUSINESS BATIK AT KENDAL - Sandi - Supaya; Umar - Farouk; Nur - Rini; Sri Eka Sadriatwati (Admisi dan Bisnis, 2017)
ABSTRACTThe shopping experience enjoyable and unforgettable is the basis of experiential marketing. All human senses to function as an input medium are taken through the sense of taste (sense), then by four other senses (feel, think, act, and relate) is processed into a pleasant and memorable experience. Model of experiential marketing is needed in abstraction and tools to decide the election priority in marketing strategies. The purpose of this study was to design experiential marketing model that can be implemented on the Small and Medium Enterprises. Survey methods used to obtain the data of research variables. Validity and Reliabelitas done to find the constructs of variables valid and reliable. Regression and correlation analysis were used to analyze the relationship between variables. The conclusion of this study are: Cognitive Sensory Marketing Experience (Sense) has a positive influence on cognitive Creative Thinking (Think), and Cognitive Creative Thinking (Think) positive influence on experiential marketing. Based on the conclusion of the study, it is advisable to increase the Cognitive Sensory Marketing Experience (Sense). Increased Cognitive Sensory Marketing Experience (Sense) will encourage creative cognitive Marketing Thought (Think), which will increase the experiential marketing in the form of shopping that good impression, and hard to forget. Keywords: experiential; fun; batik; taste; think  ABSTRAKPengalaman berbelanja yang menyenangkan dan tak terlupakan adalah dasar dari pengalaman pemasaran. Semua indra manusia berfungsi sebagai media masukan yang diambil melalui indera perasa (sense), maka oleh empat indera lainnya (merasakan, berpikir, bertindak, dan berhubungan) diolah menjadi pengalaman yang menyenangkan dan berkesan. Model pemasaran pengalaman diperlukan dalam abstraksi dan alat untuk menentukan prioritas pemilihan dalam strategi pemasaran. Tujuan dari penelitian ini adalah untuk merancang model pemasaran eksperiensial yang dapat diimplementasikan pada Usaha Kecil dan Menengah. Metode survei yang digunakan untuk memperoleh data dari variabel penelitian. Validitas dan Reliabelitas dilakukan untuk mengetahui konstruk variabel yang valid dan reliabel. Analisis regresi dan korelasi digunakan untuk menganalisis hubungan antar variabel. Kesimpulan dari penelitian ini adalah: Cognitive Sensory Marketing Experience (Sense) memiliki pengaruh positif terhadap Thinking Creative Thinking (Think), dan Cognitive Creative Thinking (Think) berpengaruh positif terhadap experiential marketing. Berdasarkan kesimpulan penelitian ini, disarankan untuk meningkatkan Cognitive Sensory Marketing Experience (Sense). Meningkatnya Cognitive Sensory Marketing Experience (Sense) akan mendorong creative cognitive Marketing Thought (Think), yang akan meningkatkan pengalaman marketing dalam bentuk belanja yang terkesan baik, dan sulit untuk dilupakan. Kata kunci: pengalaman; menyenangkan; batik; rasa; berpikir